Bio-nanotechnology : a revolution in food, biomedical, and health sciences - Bagchi, Debasis, 1954- (Chichester, West Sussex ; Ames, Iowa : Wiley-Blackwell, 2013)
'Bio-nanotechnology is the key functional technology of the 21st century. It is a fusion of biology and nanotechnology based on the principles and chemical pathways of living organisms, and refers to the functional applications of biomolecules in nanotechnology. It encompasses the study, creation, and illumination of the connections between structural molecular biology, nutrition and nanotechnology, since the development of techniques of nanotechnology might be guided by studying the structure and function of the natural nano-molecules found in living cells. Biology offers a window into the most sophisticated collection of functional nanostructures that exists. This book is a comprehensive review of the state of the art in bio-nanotechnology with an emphasis on the diverse applications in food and nutrition sciences, biomedicine, agriculture and other fields. It describes in detail the currently available methods and contains numerous references to the primary literature, making this the perfect'field guide' for scientists who want to explore the fascinating world of bio-nanotechnology. Safety issues regarding these new technologies are examined in detail.'--
Introduction. Biomedical Applications of Nanomaterials: An Overview / Sunil K Singh, Paresh P Kulkarni, Debabrata Dash -- The Challenge of Nanotechnology-Derived Food: Addressing the Concerns of the Public / Tomiko Yamaguchi -- Nanotechnology and Public Health: Contributions, Promises, and Premises / Masami Matsuda, Ayako Goto, Toshio Ogino, Yoshiaki Tanaka -- Nanotechnology in Nutrition and Medicine. Functional Nanomaterials for Biomedical Research: Focus on Bio-Functionalization, Biosynthesis, and Biomedical Applications / Murugan Veerapandian, Sathya Sadhasivam, Ramesh Subbiah, Kyusik Yun -- An Overview of Nanoparticle-Assisted Polymerase Chain Reaction Technology / Cenchao Shen, Zhizhou Zhang -- A Revolution in Nanomedicines / Iulian Bobe, Mitsunori Harada, Ichiro Nakatomi -- Nanotechnology for Regenerative Medicine / Yoshikazu Kumashiro, Masayuki Yamato, Teruo Okano -- Nanotechnology, Human Health and Applications. Novel Technologies for the Production of Functional Foods / Jack Appiah Ofori, Yun-Hwa Peggy -- Nanomedicine: The Revolution of the Big Future with Tiny Medicine / Danny D Meetoo -- Application of [gamma]-Cyclodextrin in Nanomedicinal Foods and Cosmetics / Yukiko Uekaji, Ayako Jo, Akihito Urano, Keiji Terao -- Polymer-Based Nanocomposites for Food Packaging Applications / Maurizio Avella, Roberto Avolio, Emilia Di Pace, Maria Emanuela Errico, Gennaro Gentile, Maria Grazia Volpe -- Ultrasound-Mediated Delivery Systems: Using Nano/Microbubbles or Bubble Liposomes / Kazuo Maruyama, Ryo Suzuki, Yusuke Oda, Yoko Endo-Takahashi, Yoichi Negishi -- Nanoprobes and Quantum Dots: Employing Nanotechnology to Watch Biology / Shampa Chatterjee -- Enhanced Optical Biosensors Based on Nanoplasmonics / Kyujung Kim, Youngjin Oh, Donghyun Kim -- Nano-Biosensors for Mimicking Gustatory and Olfactory Senses / Kiyoshi Toko, Takeshi Onodera, Yusuke Tahara -- Nanoparticles Inducing Simultaneous Bioreaction in Living Organisms: Critical Sizes for Transition of Biointeractive Behavior / Fumio Watari -- Analysis of Immunological Reactions to Nanoscale Foods: Possible Occurrence of Allergic Reaction to Nanoscale Food Particles / Eisuke F Sato, Maki Hashimoto, Masayasu Inoue -- An Overview of Green Nanotechnology / Kelvii Wei Guo -- Characterization of Biopolymer and Chitosan-Based Nanocomposites with Antimicrobial Activity / Jong-Whan Rhim -- Nanotechnology and its Use in Agriculture / Alejandro Perez-de-Luque, M Carmen Hermosin -- Applications of Polymeric Nanoparticles with Steroids: A Review / Megumu Higaki -- Nanocomposites for Food Packaging: An Overview / Tie Lan -- Nanotechnology in Cosmetic Products / Howard A Epstein, Alexander Kielbassa -- Potential Medical Applications of Fullerenes: An Overview / Seema Thakral, Naveen Kumar Thakral -- Nanotechnology and Other Versatile Diverse Applications. Biomedical Applications of Carbon-Based Nanomaterials / Sunil K Singh, Paresh P Kulkarni, Debabrata Dash -- Carbon Nanotubes and their Application to Nanotechnology / Wojtek Tutak, Sara Reynaud, Rajen B Patel -- Characterization of Cyclodextrin Nanoparticles as Emulsifi ers / Hiroyoshi Moriyama, Yoshihiro Saito, Debasis Bagchi -- Application of Poly(?-Glutamic Acid)-Based Nanoparticles as Antigen Delivery Carriers in Cancer Immunotherapy / Kazuhiko Matsuo, Naoki Okada, Shinsaku Nakagawa -- Basic Characterization of Nanobubbles and their Potential Applications / Seiichi Oshita, Tsutomu Uchida -- Nanomaterial Manufacturing. Formulation and Characterization of Nanodispersions Composed of Dietary Materials for the Delivery of Bioactive Substances / Takashi Kuroiwa, Jun Watanabe, Sosaku Ichikawa -- Production of Nanoscale Foods Using High-Pressure Emulsifi cation Technology / Kazuyuki Takagi -- Production of Monodisperse Fine Dispersions by Microchannel/Nanochannel Emulsifi cation / Isao Kobayashi, Marcos A Neves, Sosaku Ichikawa, Takashi Kuroiwa -- Applications of Microscopy and Nuclear Magnetic Resonance in Nanotechnology. Applications of Atomic Force Microscopy in Food Nanotechnology / Hiroshi Muramatsu, Jun'ichi Wakayama, Kazumi Tsukamoto, Shigeru Sugiyama -- Applications of NMR to Biomolecular Systems of Interactions: An Overview / Shinya Hanashima, Yoshiki Yamaguchi -- Applications in Enhancing bioavailability and Controlling Pathogens. Bioavailability and Delivery of Nutraceuticals and Functional Foods Using Nanotechnology / Hailong Yu, Qingrong Huang -- Encapsulation of Bioactive Compounds in Micron/Submicron-Sized Dispersions Using Microchannel Emulsifi cation or High-Pressure Homogenization / Marcos A Neves, Isao Kobayashi, Henelyta S Ribeiro, Katerina B Fujiu -- Nanometric-Size Delivery Systems for Bioactive Compounds for the Nutraceutical and Food Industries / Francesco Donsi, Mariarenata Sessa, Giovanna Ferrari -- Nanoemulsion Technology for Delivery of Nutraceuticals and Functional-Food Ingredients / Luz Sanguansri, Christine M Oliver, Fernando Leal-Calderon -- Nanotechnology and Nonpolar Active Compounds in Functional Foods: An Application Note / Philip J Bromley -- Safety, Toxicology and Regulatory Aspects. How Standards Inform the Regulation of Bio-nanotechnology / Martha E Marrapese -- FDA and Nanotech: Baby Steps Lead to Regulatory Uncertainty / Raj Bawa -- Toxicity and Environmental Risks of Nanomaterials: An Update / Paresh C Ray, Anant Kumar Singh, Dulal Senapati, Zhen Fan, Hongtao Yu -- Nanoparticle-Lung Interactions and Their Potential Consequences for Human Health / Craig A Poland, Martin J D Clift -- Future Directions in Bio-Nanotechnology. Bio-Nanotechnology: A Journey Back to the Future / Debasis Bagchi, Manashi Bagchi, Hiroyoshi Moriyama, Fereidoon Shahidi.
Includes bibliographical references and index.
Print version record.
Keywords: Biomedical engineering; Nanotechnology; Nanotechnology; Biomedical Technology; Biomimetic materials; Food technology; MEDICAL -- Instruments & Supplies; Biomedical engineering; Nanotechnology; Electronic books